What is the global perspective on advanced practice physiotherapy: A qualitative study across five countries - Andrews K. Tawiah; Marguerite Wieler; Jordan Miller; Alison Rushton; Linda Woodhouse (PLoS ONE, 2025)
Background Despite the growth of advanced practice physiotherapy (APP) and the evidence of its effectiveness, challenges persist in implementing and sustaining this model of care. The main challenge is the lack of a universally accepted definition. The lack of a clear understanding of what APP is, who can become advanced practice physiotherapists, and the required educational qualifications leads to widespread confusion among patients, employers, and healthcare providers. Aim Our study aims to explore the global perspectives of advanced practice physiotherapy. Objectives: 1.To understand how APP is defined and develop a common definition across countries. 2.To understand the difference between APP and clinical specialists. 3.To understand the clinical practice challenges of working as an advanced practice physiotherapist. Methods A qualitative descriptive study was carried out through four online focus groups with participants from Australia, Canada, Ireland, New Zealand, and the United Kingdom. Participants were selected using purposive sampling, and the focus groups were recorded, transcribed and analyzed. An initial coding framework was developed by two coders, with subsequent coding performed by one of the coders. Data were analyzed using reflective thematic analysis and reported following the Standards for Reporting Qualitative Research (SRQR). Results Sixteen participants were recruited, twelve were advanced practice physiotherapists, and four were leaders or researchers. Three major themes were developed: (1) Advanced practice physiotherapists have a higher clinical expertise and a high level of responsibility, (2) Advanced practice physiotherapists are distinct from specialists based on the competencies, scope, and regulation, (3) Professional and operational challenges are associated with APP. Ten (10) sub-themes associated with the major themes were developed and presented in a thematic map. Conclusion This study provided a common definition of APP, distinguished advanced practitioners from clinical specialists, and discussed challenges to implementation. The study explores the complexities of APP and specialization, emphasizing the obstacles faced by practitioners. The proposed definition can be tailored to meet the specific requirements of local and regional healthcare needs. Addressing the challenges to implementation could support the sustainability of the APP model of care.